Searches for rare nuclear decays in the LUX-ZEPLIN experiment - Al Musalhi, AK (2023)
The fundamental nature of dark matter stands as one of the greatest mysteries in physics. A compelling body of evidence indicates that dark matter accounts for 84% of the total matter density of the universe, and yet the detection of its constituent particles remains elusive. Stationed deep underground, the LUX-ZEPLIN (LZ) experiment utilises several tonnes of xenon in a dual-phase time projection chamber to conduct direct searches for particle dark matter. A world-leading limit was recently set by the LZ experiment for interactions between nucleons and weakly interacting massive particles, the most promising dark matter candidate. The work of this thesis leverages the unprecedented sensitivity and versatility of the LZ detector to expand the scientific programme to searches for rare phenomena beyond dark matter.